Analisa Fitokimia dan Kandungan Bahan Aktif dari Lima Aksesi Tanaman Handeuleum (Graptophyllum pictum (L.) Griff) - Feri Manoi (Politeknik Negeri Lampung., 2011)
Handeuleum ( Graptophyllum pictum (L.) Griff) constituting acknowledged dill useful to cure some types disease as pile. This plant have color pattern performance leaf which variably. This research is done at Observational Hall examination laboratory Dill and Achromatic, Bogor in july until September 2008. To the effect research is get phytochemical content picture and active component of 5 accession handeleum's plants. Phytochemical is obstetric analysis (alkaloid, saponin, tanin, glikocide, flavonoid, fenolik, triterpenoid, steroid) done at Observational Hall Examination Laboratory Dill and Achromatic (Balitro) Bogor, meanwhile GC MS'S analysis is done at Laboratory Dopes Jakarta. Of compound analysis result phytochemical is gotten that 5 accession handeuleum contain alkaloid's compounds, saponin, tanin, glikosida with notation 4 + or herculean. Accession with patterns green leaf turn white at green erect periphery and brown have phytochemical content same, while accession with colour patterns green leaf turn white to be intermediated have flavonoid's content is contemned 2 +. Of GCMS'S analysis result apparently exhaustive accession handeleum contains kindred active component with vitamin e,Neophytadiene, tocopherol's gamma, Ergost - 5 en 3 ol (3. beta.) and stigmast - 5 en 3 ol. Key words: Graptophyllum pictum, phytochemical, active component, accession